Business Model Canvas : Budu Filter Container / Nabila Husna Mohamad Rodzi - Mohamad Rodzi, Nabila Husna (2020)
This is the BMC report for my company product which is the Budu Filter Container where it can act as the business plan. It is interesting note that although the focus of the BMC is to establish the foundation of business model, it also may help my company to further improve my business plan